Effects of Lateral Variation in Vegetation and Basin ‘Dome’ Shape on Tropical Lowland Peat Stabilisation in the Kota Samarahan-Asajaya Area, West Sarawak, Malaysia - Zulkifley, Mohamad Tarmizi Mohamad; Ng, Tham Fatt; Raj, John Kuna; Hashim, Roslan; Ashraf, Muhammad Aqeel (Wiley, 2014)
Field surveys indicate lateral variation in peat humilIcation levels (von Post) in dominantly occurring fibric, fibric to hemic, sapric and hemic to sapric peats across a gradient from the margin towards the centre of tropical lowland peat domes. Cement-peat stabilisation can be enhanced by adding mineral soil fillers (silt, clays and line sands) obtained from Quaternary floodplain deposits and residual soil (weathered schist). The unconfined compressive strength (UCS) of the stabilised cement-mineral soil filler-peat mix increases with the increased addition of selected mineral soil filler. Lateral variation in the stabilised peat strength (UCS) in the top 0 to 0.5 m layer was found from the margin towards the centre of the tropical lowland peat dome. The variations in the UCS of stabilised tropical lowland peats along a gradient from the periphery towards the centre of the peat dome are most likely caused by a combination of factors due to variations in the mineral soil or ash content of the peat and horizontal zonation or lateral variation in the dominant species of the plant assemblages (due to successive vegetation zonation of the peat swamp forest from the periphery towards the centre of the tropical lowland peat dome). © 2014 Geological Society of China.